Legal argumentation of corporate criminal liability for trading cryptocurrency e-dinar coin (EDC) with ponzi scheme - Weshley Gde Putra Cahyono; Yana Indawati (International Journal on Social Science, Economics and Art, 2023)
The development of technology, information, and industry 4.o, this has an impact on the increasing economic needs of the community, with this development indirectly encouraging the economy in the industrial sector, more and more corporations are carrying out business activities in the field of cryptocurrency trading where the rules for this activity are still gray in Indonesia, and can cause criminal acts including fraud, and fraudulent investment. Therefore, criminal acts on cryptocurrency trading e-dinar coin (edc) with ponzi schemes carried out by corporations must be taken seriously to protect and provide accountability to the people of Indonesia, according to the author's analysis, the unclear rules of Tranding cryptocurrency with ponzi schemes carried out by corporations, influenced by law enforcement factors that are still not perfect to fulfill justice in society, therefore there is still a need for laws that explicitly regulate cryptocurrency trading activities with ponzi schemes carried out by corporations, as well as a criminal liability system in corporate criminal acts with ponzi schemes if associated with the theory of corporate liability systems, then those who can be held criminally responsible and bear are corporations and administrators because if only punishing one is not enough to bring a sense of justice and security in society